Platinum loaded cyclomatrix polyphosphazene submicrospheres improve fire retardancy of epoxy with very low addition. (February 2019) - Guo, Xiaodong; Geng, Xiaowei; Gao, Xiangdi; Zhang, Xin; Yang, Danqi; Xu, Jianzhong; Ma, Haiyun
Abstract: Platinum nanoparticle loaded polyphosphaziene submicrosphere (Pt-PPS) was synthesized via the reduction of chloroplatinic acid on the surface of PPS microspheres. Pt nanoparticles were dispersed uniformly with an average particle size of 2 nm from the SEM and TEM investigation. The cone calorimeter tests showed that a very low Pt incorporation (0.15%) can significantly improve the flame retardancy of epoxy resin (EP). The heat release rate (HRR) and total heat release (THR) were reduced by 40.2% and 23.2%, respectively. The improvement in flame retardancy is contributed by the catalytic carbonization effect of Pt synergizing with PPS submicrospheres. Highlights: Platinum nanoparticle loaded polyphosphaziene submicrosphere synthesized. Significant flame retardancy exhibited with very low addition (0.15%) of Platinum. Catalytic carbonization effect of Platinum improve fire retardancy of epoxy.